Implementing Salesforce in the Nonprofit Sector-Challenges and Solutions - Sanjay Gorantla (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Although this study focuses on the effectiveness of Salesforce's Nonprofit Success Pack (NPSP) in improving nonprofit organizations' operational capabilities, it examines several case studies. It captures the transformative impacts on donor management capabilities and operational efficiencies brought about by Salesforce. Despite these pros, nonprofits face challenges, including high implementation costs, a steep learning curve, and challenges in system integration. To counter these challenges, the paper offers actionable solutions like the proper allocation of resources and an outline of training frameworks. It also highlights areas for further research, especially the potential of leveraging artificial intelligence to enhance the functionalities of CRM. These revelations highlight the essential contribution of cutting-edge CRM frameworks in revolutionizing charity functions, offering instrumental takeaways for associations keen on utilizing technology for additional influence.